CSF3 enhances the innate immune responses to ALV-J infections via NF-κB and interferon pathways - Junliang Xia; Weiding Chen; Chengxun Xu; Meihuizi Wang; Guodong Mo; Xiquan Zhang (Poultry Science)
Avian leukosis viruses (ALVs) are a group of retroviruses with immunosuppressive and tumorigenic effects, causing substantial economic losses to the poultry industry due to the lack of effective commercial vaccines and antiviral drugs. Granulocyte colony-stimulating factor 3 (CSF3) is a cytokine that regulates hematopoiesis and modulates the proliferation and differentiation of immune cells. In our previous study, we unexpectedly observed that CSF3 expression was significantly upregulated upon stimulation with interferon-α (IFN-α) and ALV, suggesting a potential role in ALV infection. In this study, we confirmed that the CSF3 promoter could be activated by ALV and polyinosinic-polycytidylic acid (poly I:C) using a CSF3 promoter-driven reporter construct, and GAS potentially serving as the response element. Phylogenetic analysis showed that avian and mammalian CSF3 genes clustered separately within the phylogenetic tree. Subsequently, we overexpressed and silenced CSF3 in DF-1 cells followed by ALV-J infection. Transcriptome analysis revealed that CSF3 overexpression significantly upregulated genes involved in antiviral and inflammatory responses, particularly those in the TLR, RIG-I, JAK/STAT, and NF-κB signaling pathways. Our results demonstrated that CSF3 induced the expression of IFNs and antiviral genes (IRF7, Mx, MDA5, OASL, and ACSL1). Furthermore, CSF3 improved the phosphorylation level of IκBα, leading to the production of pro-inflammatory cytokines and activation of the NF-κB pathway, ultimately suppressing ALV-J envelope glycoprotein expression. Notably, the pro-inflammatory and antiviral effects of CSF3 were abolished upon treatment with a STAT3 inhibitor, suggesting that CSF3 exerts its antiviral function through STAT3 phosphorylation. A similar effect of CSF3 was observed in primary fibroblasts derived from chicken embryos. Collectively, our findings indicate that CSF3 may function as an atypical interferon-stimulated gene (ISG), enhancing the immune response against ALV-J by activating the NF-κB signaling pathway and interferon-mediated antiviral mechanisms. These results not only reveal the antiviral role of CSF3 but also provide new insights into the host's innate immune response to ALV. Furthermore, they highlight the potential of CSF3 as a candidate resistance gene for breeding programs or as a vaccine adjuvant for disease prevention.